Sugar or Fat?—Metabolic Requirements for Immunity to Viral Infections - Shehata, Hesham M.; Murphy, Andrew J.; Lee, Man kit Sam; Gardiner, Clair M.; Crowe, Suzanne M.; Sanjabi, Shomyseh; Finlay, David K.; Palmer, Clovis Steve (Frontiers in Immunology, 2017)
The realization that an intricate link exists between the metabolic state of immune cells and the nature of the elicited immune responses has brought a dramatic evolution to the field of immunology. We will focus on how metabolic reprogramming through the use of glycolysis and fatty-acid oxidation (sugar or fat) regulates the capacity of immune cells to mount robust and effective immune responses. We will also discuss how fine-tuning sugar and fat metabolism may be exploited as a novel immunotherapeutic strategy to fight viral infections or improve vaccine efficacy.